Cholinergic Circuit Control of Postnatal Neurogenesis - Asrican, Brent; Páez-González, Patricia; Erb, Joshua; Kuo, Chay T (Taylor & Francis, 2016)
New neuron addition via continued neurogenesis in the postnatal/adult mammalian brain presents a distinct form of nervous system plasticity. During embryonic development, precise temporal and spatial patterns of neurogenesis are necessary to create the nervous system architecture. Similar between embryonic and postnatal stages, neurogenic proliferation is regulated by neural stem cell (NSC)-intrinsic mechanisms layered upon cues from their local microenvironmental niche. Following developmental assembly, it remains relatively unclear what may be the key driving forces that sustain continued production of neurons in the postnatal/adult brain. Recent experimental evidence suggests that patterned activity from specific neural circuits can also directly govern postnatal/adult neurogenesis. Here, we review experimental findings that revealed cholinergic modulation, and how patterns of neuronal activity and acetylcholine release may differentially or synergistically activate downstream signaling in NSCs. Higher-order excitatory and inhibitory inputs regulating cholinergic neuron firing, and their implications in neurogenesis control are also considered.
Keywords: Desarrollo neurológico; Receptores colinérgicos; Neuroplasticidad; Acetylcholine; Ach; Adult neurogenesis; ChAT neuron; SVZ; SGZ; SEZ; Cholinergic circuit; Neurogenic niche